Adverse neonatal outcome associated with maternal tuberculosis in a public tertiary centre: a retrospective cohort study - Zainudin, Zurina; Nunis, Melissa Anne; Abang Abdullah, Aisha Fadhilah; Osman, Malina; Zakaria, Noorzeehan (Malaysian Medical Association, 2025)
Introduction: The aim of this study was to evaluate a group of infants born to women with tuberculosis (TB) during pregnancy to determine the neonatal morbidities and its outcomes associated with tuberculosis in pregnancy. Materials and Methods: Data from January 2007 to December 2021 was collected for analysis as part of a retrospective cohort study. This study was conducted in a tertiary public hospital in Malaysia, Hospital Sultan Idris Shah (HSIS). Cases were identified from the hospital’s bacille Calmette-Guerin (BCG) vaccination notification forms and merged with records from the neonatal intensive care unit’s census. Controls were infants born to mothers unaffected by TB within the same hospital and year as the index case (1:4 ratio). Descriptive statistics and logistic regression were used to analyse the data. The main outcome measures were the risk of congenital tuberculosis, premature birth, low birth weight, small for gestational age and low APGAR score. Results: Infants born to mothers with TB exhibited a twofold increased risk of low birth weight (Odds Ratio, OR: 2.51; 95% Confidence Interval, 95%CI: 1.31, 4.81), with an even higher risk (OR: 3.29; 95%CI: 1.637, 6.612) if active TB was diagnosed during the index pregnancy. These infants also had an elevated risk of being small for gestational age compared to infants born to healthy mothers (OR: 2.48; 95%CI:1.15, 5.39). Furthermore, adverse outcomes were also more frequently detected among infants of mothers with pulmonary TB compared to those with extra-pulmonary TB. Infants born to mothers with PTB were more likely to be born with low birth weight (OR: 1.60; 95%CI: 1.095, 2.339). No cases of congenital TB were reported throughout the entire study period.